2012
DOI: 10.1075/sll.15.1.05hal
|View full text |Cite
|
Sign up to set email alerts
|

Phonological similarity judgments in ASL

Abstract: We created a novel paradigm to investigate phonological processing in sign and asked how age of acquisition (AoA) may affect it. Participants indicated which of two signs was more phonologically similar to a target, and estimated the strength of the resemblance with a mouse click along a continuous scale. We manipulated AoA by testing deaf native and non-native signers, and hearing L2 signers and sign-naïve participants. Consistent with previous research, judgments by the native and L2 signers reflected simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In another study, native deaf and L2 hearing signers did not differ in their phonological similarity judgments for pairs of ASL signs. However, non-native deaf signers showed phonological similarity ratings that differed from those of both the native deaf and L2 hearing ASL learners, but not from those made by sign-naïve hearing participants (Hall, Ferreira & Mayberry, 2012). In a third study, native deaf and L2 hearing signers performed similarly on a gated sign recognition task (Morford and Carlson, 2011).…”
Section: Aoa Effects On Asl Outcomementioning
confidence: 84%
“…In another study, native deaf and L2 hearing signers did not differ in their phonological similarity judgments for pairs of ASL signs. However, non-native deaf signers showed phonological similarity ratings that differed from those of both the native deaf and L2 hearing ASL learners, but not from those made by sign-naïve hearing participants (Hall, Ferreira & Mayberry, 2012). In a third study, native deaf and L2 hearing signers performed similarly on a gated sign recognition task (Morford and Carlson, 2011).…”
Section: Aoa Effects On Asl Outcomementioning
confidence: 84%
“…The pioneering research of Rachel Mayberry and her colleagues has shown that language experience with a sign language facilitates the acquisition of spoken language (Hall, Ferreira, & Mayberry, 2012;Mayberry, Lock, & Kazmi, 2002). The pioneering research of Rachel Mayberry and her colleagues has shown that language experience with a sign language facilitates the acquisition of spoken language (Hall, Ferreira, & Mayberry, 2012;Mayberry, Lock, & Kazmi, 2002).…”
Section: Cross-modal Projectionsmentioning
confidence: 99%
“…The pioneering research of Rachel Mayberry and her colleagues has shown that language experience with a sign language facilitates the acquisition of spoken language (Hall, Ferreira, & Mayberry, 2012;Mayberry, Lock, & Kazmi, 2002). Indeed, early exposure to a sign language (in Hall et al, 2012;Mayberry et al, 2002) can offer social and cognitive benefits, and the constraints on the interpretation of signs (Strickland et al, 2015) could be explained not by grammatical principles but by iconicity. These results, however, do not directly establish whether cross-modal transfer is due to the projection of grammatical principles, specifically.…”
Section: Cross-modal Projectionsmentioning
confidence: 99%
See 2 more Smart Citations